Vine shoot-derived hard carbons as promising anodes for sodium-ion batteries: valorization of pig manure as HTC solvent - Alvira Dobón, Darío; Antorán, Daniel; Sebastian, Victor; Manyà, Joan J. (Jornada de Jóvenes Investigadores del I3A, 2023)
Sodium-ion batteries (SIBs) are one of the most promising candidates to replace lithium-ion batteries (LIBs) in grid-scale energy storage applications. The design of high-performance anodes and the fully understanding of the sodium storage mechanisms are the main bottleneck to overcome. Herein, a vine shoot-based hard carbon anode was synthesized via hydrothermal carbonization followed by a pyrolysis step (800 to 1200 °C). In addition to water, pig manure and diluted hydrochloric acid were tested as reaction media.